Cloud Storage Monitoring System using File Access Pattern - Augustus Devarajan A, Mr.; SudalaiMuthu T, Dr. (International Journal of Engineering and Technology, 2018)
Cloud computing is important on current demanding business requirements and it has been emerged as unavoidable technology. The usage of memory storage for Cloud Computing IaaS Service is expanding exponentially every year. The cloud storages are used by the cloud user due to less storage cost compare with other storage methods. The replication of files provides high availability, reliability. It helps in attractive the data availability which reduces the overall access time of the files, but at the same time it occupies more storage space and yielded high storage cost. The cloud user holds storage space twice than which is needed. It is a dire need of a system to find unwanted files in the cloud and the frequency of file access in order to optimize the storage space in cloud. This paper proposed a system, Cloud Storage Monitoring (CSM) system, which is monitoring the IaaS storage usage and analyzes the file access patterns to identify the frequency of access, size, future access prediction, replication of files in the cloud storage. The proposed system generates a ranking for each file which predicts future access pattern. The CSM system generates a report to the user to rearrange or delete or archive the files to eliminate duplicate files in the cloud storage and increase the availability of the files. The CSM system is experimented in the CloudSim environment, the results showed that the availability have been increased and the storage space is reduced as 10.91% lower than the normal system. Â Â